A STUDY OF SYNTACTIC AND SEMANTIC FEATURES OF ENGLISH HUMAN MOTION VERBS IN AMERICAN MOVIES AND THEIR VIETNAMESE TRANSLATIONAL EQUIVALENTS - Dương Thị Duyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis is designed to investigate English human motion verbs in American movies and their Vietnamese translational equivalents on the aspect of the syntactic as well as the semantic features. The methods selected to analyze the syntactic and semantic features are Descriptive method, Interpretive method and Contrastive method .The purpose of this research is presenting commonly used English human motion verbs, the differences and similarities between English human motion verbs and their Vietnamese translational equivalents are considered. Causes are also dealt with the implications for teaching and learning, translating and especially for students and translators in movie industry. Simultaneously, some further researches are also suggested in this thesis.